2018
DOI: 10.1186/s12936-018-2521-0
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping a Plasmodium transmission spatial suitability index in Solomon Islands: a malaria monitoring and control tool

Abstract: BackgroundMalaria remains a challenge in Solomon Islands, despite government efforts to implement a coordinated control programme. This programme resulted in a dramatic decrease in the number of cases and mortality however, malaria incidence remains high in the three most populated provinces. Anopheles farauti is the primary malaria vector and a better understanding of the spatial patterns parasite transmission is required in order to implement effective control measures. Previous entomological studies provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Additionally, although a positive excreta result would not be sufficient to suggest that the mosquitoes in the trap are transmitting Plasmodium , it would indicate that the parasite is circulating. However, together with geolocation and mapping of larval habitats and areas of human activity [50], a positive result can be used to identify potential foci of transmission. This is particularly interesting in low transmission settings or to monitor re-establishment after elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although a positive excreta result would not be sufficient to suggest that the mosquitoes in the trap are transmitting Plasmodium , it would indicate that the parasite is circulating. However, together with geolocation and mapping of larval habitats and areas of human activity [50], a positive result can be used to identify potential foci of transmission. This is particularly interesting in low transmission settings or to monitor re-establishment after elimination.…”
Section: Discussionmentioning
confidence: 99%
“…In Solomon Islands, RS and GIS technologies were also exploited and used to map a Plasmodium transmission's spatial suitability index [19]. Jeanne et al suggested that remote sensing images can translate environmental preferences (e.g., availability of water sources, elevation, and distance to coastline) of Anopheles farauti into geolocated information.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of the SD and CTK NS1 RDTs for DENV-3 detection was similar to that in our previous study, in which the sera were collected from a 2013 DENV-3 dengue outbreak in the Solomon Islands ( S1 Table ) [ 24 ]. However, the inclusion of anti-DENV IgG in the CTK NS1 RDT largely decreased the specificity, which might be due to the assay being very sensitive to the presence of low levels of IgG induced in previous DENV infections, or the assay might cross-reactive with the IgG induced by vaccination (e.g., JEV in Taiwan) [ 48 , 49 ] or infection with other flaviviruses or malaria, especially in the Solomon Islands [ 50 – 52 ]. RT-PCR has been recommended for confirmational diagnosis of dengue virus infection, allowing for early intervention for surveillance, outbreak investigations, and clinical management.…”
Section: Discussionmentioning
confidence: 99%